Unique phenomenon of H5 highly pathogenic avian influenza virus in China: co-circulation of Clade 2.3.4.4b H5N1 and H5N6 results in diversity of H5 Virus - Xinkui Zhang; Yujia Yang; Xinyu Han; Dandan Wei; Beibei Niu; Qiuhong Huang; Yan Li; Huifang Yin; Xianpeng Zhang; Ming Liao; Weixin Jia (Emerging Microbes and Infections)
Recently, Clade 2.3.4.4b H5N1 virus has been widely prevalent globally. Although no outbreaks of Avian Influenza have occurred in poultry in China recently, Clade 2.3.4.4b H5 virus can still be isolated from wild birds, live poultry markets and environment, indicating the ongoing co-circulation of H5N1 and H5N6 viruses. In this study, phylogenetic analysis of global Clade 2.3.4.4b viruses and 20 laboratory-isolated H5 strains revealed that Chinese H5N1 and H5N6 viruses since 2021 cluster into two distinct groups, G-I and G-II. Bayesian phylodynamic analysis reveals that G-I H5N6 virus has become an endemic virus in China. In contrast, G-II H5N1 virus, with South China as its main epicentre, has been disseminated in China and its surrounding countries, with its transmission more reliant on the connections of wild birds and waterfowl. Reassortment analysis indicates that since 2023, Clade 2.3.4.4b H5 viruses isolated in China have formed seven genotypes. The genome of H5 viruses has undergone changes compared to those previously prevalent in China. Animal experiments have shown that prevalent H5 viruses exhibit significant lethality in chickens. Additionally, certain H5 viruses have shown the capability of systemic replication in mice. It is noted that H5N6 viruses with HA genes derived from H5N1 viruses demonstrate stronger virulence and pathogenicity in chickens and mice compared to G-I H5N6 viruses. Our study indicates that the co-circulation of H5N1 and H5N6 viruses in China has increased the diversity of H5 viruses, making continuous surveillance of H5 viruses essential.